Kajian Warna : kecenderungan pemilihan warna oleh kanak-kanak - Mohd., F.L (University Malaysia Sarawak, UNIMAS., 2006)
Color plays an important rule in our lives especially for the children. Children is an individual who using the colors to recognize an objects. Studies on colors have been done to recognize and analyze the application of colors and motifs according to the children's choice. This finding will be applied in bed sheets.